Adult-onset Still's Disease as a Differential Diagnosis in Prolonged Fever: Diagnosis and Treatment Experience - Felix F Widjaja; Diah Martina; Soroy Lardo; Suryo Anggoro K Wibowo (Interna Publishing, 2019)
Adult onset Still's disease is a rare systemic disease that may involve many organs and may mimick many disease such as infection, autoimmune disease, and also malignancy. The diagnostic approach and treatment strategies have not been well established due to its rarity; however, there are some diagnostic criteria that may help. We present a case of 36-year old man who experienced high prolonged fever which firstly thought as infection. He also had unilateral wrist and knee joint pain and maculopapular rash. Laboratory examination showed high leukocytes count with elevated polymorphonuclear neutrophil count, high platelet count, high ferritin level, and negative results of many infection markers (typhoid antibody, procalcitonin, malaria test, blood culture, urine culture, IgM pneumonia, ASTO, syphilis test, antiHIV, HBsAg, antiHCV, etc). Chest X-ray, joint X-ray, ultrasonography, and echocardiography showed normal result. The patient was then diagnosed with Adult-onset Still's disease and received intravenous methylprednisolone and the fever was disappeared in 3 days. Six months later the arthralgia appeared again, methotrexate was administered and the pain was then relieved.